Comparative Study of Homestay Room Pricing in Munduk and Pinge Tourism Villages, Bali - Wiryanata, I Gusti Ngurah Agung; Darmaputra, Putu Gde Eka; Suprastayasa, I Gusti Ngurah Agung; Sunarsa, I Wayan; Arnata, Rusdi (Program Studi Manajemen Divisi Kamar, 2025)
Homestays as the main form of accommodation in tourist villages have a strategic role in creating authentic experience for tourists while improving the welfare of the local community. In order to maximize the income and the sustainability of the business, pricing should be done in careful way taking into account all aspects such as room facilities, amenities and food and beverage served for breakfast. This study aims to compare the standard of room facilities, food and beverage standards for breakfast, and homestay pricing methods in Munduk and Pinge Tourism Villages, Bali. The research method used is a comparative study with a qualitative approach through observation, interviews, and documentation. The results of the study show that homestays in Munduk have more modern standards of facilities and breakfast with a more structured pricing method. Meanwhile, homestays in Pinge offer a local experience with simpler amenities and flexible pricing. These differences reflect different market segmentation and management approaches in each tourist village. This study recommends improving service standards, pricing transparency, and training for homestay managers to encourage sustainability and competitiveness of tourist villages.